A comparison of the efficacy of acetylcholinesterase reactivators against cyclohexyl methylphosphonofluoridate (GF agent) by in vitro and in vivo methods - Kassa, J; Cabal, J (Pharmacology & toxicology, 1999)
The purpose of this study was to compare the therapeutic efficacy of a new acetylcholinesterase reactivator, designated BI-6 (1-(2-hydroxyiminomethylpyridinium)-4-(4-carbamoylpyridinium )-2-butene dibromide), with presently used oximes (pralidoxime, obidoxime, methoxime) and H-oximes (HI-6, HLö-7) by in vitro and in vivo methods. In vitro, methoxime seems to be the most efficacious reactivator of GF agent-inhibited acetylcholinesterase because the phosphorylation of acetylcholinesterase by GF agent markedly increases its affinity for the enzyme. The oxime BI-6 is more efficacious than other presently used oximes (pralidoxime, obidoxime) but its reactivating efficacy does not reach the efficacy of H-oximes tested. On the other hand, obidoxime and pralidoxime appear to be very poor reactivators of GF agent-inhibited acetylcholinesterase because the phosphonylation of acetylcholinesterase by GF agent markedly decreases their affinity to the enzyme. In vivo, H oximes (HI-6, HLö-7) are the most efficacious antidotes for the treatment of acute poisoning with GF agent in rats while the presently used oximes such as pralidoxime and obidoxime are practically ineffective. BI-6 and methoxime are more efficacious than pralidoxime and obidoxime, nevertheless their therapeutic efficacy does not reach the efficacy of H oximes. Our results show that the ability of oximes to reactivate GF agent-inhibited acetylcholinesterase in vitro usually corresponds to their therapeutic effects against GF agent in vivo.
Keywords: Animals; Acetylcholinesterase; Rats; Rats, Wistar; lékové interakce; Drug Interactions; Atropine; Organophosphorus Compounds; oximy; In Vitro Techniques; Pyridinium Compounds; pyridinové sloučeniny; techniky in vitro; organofosforové sloučeniny; míra přežití; Enzyme Reactivators; Oximes; Male; acetylcholinesterasa; krysa rodu Rattus; Survival Rate; zvířata; mužské pohlaví; cholinesterasové inhibitory; atropin; Cholinesterase Inhibitors; enzymové reaktivátory; potkani Wistar